Sustainable Development Issues in Chemistry Learning as Educational for Sustainable Development Implementation: A Systematic Literature Review - Anggraeni, Lely; Rohaeti, Eli (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aims to systematically synthesize research articles on the application of Educational for Sustainable Development (ESD) in chemistry learning based on their suitability with the research theme: sustainable development issues, ESD dimensions, SDGs, and chemistry concepts. The urgency of this research is to explore the potential of sustainable development issues in chemistry concepts as an implementation of ESD to help teachers who experience difficulties in integrating sustainable development issues into chemistry concepts. This research was conducted with a systematic literature review design that synthesized 23 articles from the ERIC, Science Direct, and Google Scholar databases using the keywords "ESD in Chemistry Learning" and "Implementation of ESD". The results of the systematic review raised six sustainable development issues used in chemistry learning: the use of conventional and biodegradable plastics, green pesticide use, green experiments, water pollution and scarcity, biodiesel from palm oil, and others. The environmental dimension is studied more often than the economic and social dimensions of ESD application in chemistry learning. The implementation of ESD has made the greatest contribution to SDG 4 (Quality Education) with six chemistry concepts that are often used to integrate sustainable development issues: acids and bases, thermochemistry, the periodic table of elements, macromolecules, reaction kinetics, and green chemistry. The variety of sustainable development issues, ESD dimensions, SDGs, and chemical concepts used in the application of ESD in chemistry learning shows that there are opportunities for chemistry learning to contribute to sustainable development.